Back to normal? The future of global production networks - Olivier N. Godart; Holger Görg; Dennis Görlich (The crisis and beyond, 2009)
It is neither likely nor desirable for central banks to exit from unconventional monetary policies in the near future. However, it is important that central banks develop an exit strategy, evaluate the merits of new and old monetary policy tools and communicate with the public so as to maintain financial stability, support economic growth and minimize future inflationary risks. Central bank communication policy will turn out to be crucial and more challenging than it was before the crisis.
Keywords: 330; Wertschöpfung; Outsourcing; Business Network; Offshoring; Globalisierung; Wirtschaftskrise